"Colored men" and "hombres aquí" : Hernández v. Texas and the emergence of Mexican-American lawyering - Olivas, Michael A. (Hispanic civil rights series., 2006)
This collection of essays, published as part of the Hispanic Civil Rights Series, sheds light on an important civil rights case that has been overshadowed by the more compelling case, Brown v. Board of Education. It details the first case tried by Mexican Americans before the U.S. Supreme Court.